Dreamwork and imaginal healing: the incorporation of artwork in a systematized method of group dreamwork - Euvrard, Gwenda Joan (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
This exploratory study investigated the expansion of an established systematized group dreamwork method (Shuttleworth-Jordan, 1995) to incorporate artwork. The rationale for the addition of artwork was situated firstly, in a poetic Jungian understanding of the image as a holistic "place" of gnosis or transformative healing and, secondly, in an argument that in order to carry the gnostic potential of the image into the lived world, a dreamwork method should involve all four styles of consciousness (thinking, intuition, sensation and feeling). It was considered that the verbal interpretive Shuttleworth-Jordan method would be enhanced by the incorporation of a visual artwork process in order more fully to open the potential of the method for incorporating the nonverbal intuitive, sensation and feeling styles of consciousness. In order to compare the established method (dreamwork Without Art) and the proposed method (dreamwork With Art), two dreamwork workshops were conducted in which all participants experienced all four conditions of the study: Dream Presenter Without Art, Dream Presenter With Art, Group Member Without Art, Group Member With Art. Two levels of assessment were utilized: a quantitative analysis (involving rating scales completed after each dreamwork session), supported by a qualitative analysis (involving written questionnaires completed at the end of the workshops and follow-up interviews conducted a week after completion of the workshops). The results suggested that the incorporation of artwork in the Shuttleworth-Jordan (1995) group dreamwork method enhanced the established method in that a consistent trend of increased involvement in the dreamwork process and increased dreamwork effectiveness was reflected, while no deleterious effects were noted which might detract from the effectiveness of the existing model which had been established in previous research studies. Finally, a refined step-by-step group dreamwork method incorporating artwork was proposed, which included qualitative feedback from the present study.
Keywords: Dreams -- Therapeutic use; Art therapy; Jungian psychology